An assessment of the role of small scale irrigation on food security in drought prone areas in Zimbabwe: the case of Chivi district of Zimbabwe - Tagwireyi, Spencer (Midlands State University, 2017)
The study serves to unpack the role of small scale irrigation projects in ensuring food security in ward 11 of Chivi District. The study gave special attention on how the small scale irrigation schemes are implemented in the area, their role in ensuring food security in drought prone areas and the challenges that affect effective irrigation production. Qualitative and quantitative research methods were used in order to gather the information. The target sample for the qualitative approach was the farmers, community leaders as well as government workers from EMA and AGRITEX whilst the quantitative approach targeting the farmers. Chapter one of the study covers the background of the study. The second chapter discussed related literature on the implementation of irrigation schemes in Zimbabwe, their contribution to food security and the challenges affecting their development. Research methodology is presented in chapter three showing how the data was collected while chapter four present, interpret and analyses the research findings. Chapter five concludes the research and provides recommendations. The main contributions of irrigation projects found includes food production, income which also promote education and health, infrastructure development and peace promotion. However, the major challenges affecting irrigation development includes lack of finance, equipments, knowledge and farming skills, climate related disasters as well as animals and diseases that destroy the crops. From the conclusion and recommendations, the research indicated that small scale irrigation projects play an important role in ensuring food security in drought prone areas despite the existence of many challenges that tries to obstruct progress and irrigation performance.